The Lethal Nexus: Sarcopenic Obesity and the Prospective Risk of All-Cause and Cardiovascular Mortality in Older Adults-A Systematic Review and Meta-Analysis of Longitudinal Cohort Studies - Muhammad Ridho Azhari; Roza Mulyana (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: The concurrent presence of excess adiposity and low muscle mass, termed sarcopenic obesity (SO), is an emerging geriatric syndrome hypothesized to confer a greater mortality risk than either condition alone. However, the precise magnitude of this risk remains poorly quantified. This systematic review and meta-analysis aimed to synthesize evidence from longitudinal cohort studies to determine the association between SO in older adults and the risk of all-cause and cardiovascular mortality. Methods: A systematic search was conducted in PubMed, Embase, and Scopus for longitudinal cohort studies published between January 2015 and August 2025 that evaluated mortality risk in older adults (mean age ≥60 years) with SO. The primary outcomes were all-cause and cardiovascular mortality. A random-effects model was used to pool Hazard Ratios (HRs) and 95% Confidence Intervals (CIs). Heterogeneity was assessed using the I2 statistic. Results: From 2,450 records identified, eight cohort studies met the inclusion criteria, encompassing 45,280 community-dwelling older adults with a mean follow-up of 8.2 years. Compared to a reference group of non-sarcopenic, non-obese individuals, sarcopenic obesity was associated with a significantly increased risk of all-cause mortality (Pooled HR: 1.58, 95% CI: 1.42–1.76, p < 0.0001). The risk for cardiovascular mortality, assessed in six studies, was even more pronounced (Pooled HR: 1.75, 95% CI: 1.55–1.98, p < 0.0001). Moderate heterogeneity was observed for the all-cause mortality analysis (I2 = 55%), which was partially explained by differences in diagnostic criteria. Conclusion: Sarcopenic obesity is a potent predictor of both all-cause and cardiovascular mortality in older adults, conferring a risk substantially greater than a healthy state. These findings underscore the critical need for routine screening and targeted interventions to address this lethal combination of poor body composition in aging populations.